Qualitative Online Interview in Education: A Voice of Preservice Elementary School Teachers' Concerns and Questions - Shidiq, Galih Albarra; Ramdani, Zulmi (IJCAR: Indonesian Journal of Classroom Action Research, 2024)
Interviewing is the leading approach used for gathering information in qualitative research. The online interview study explores the concerns and questions expressed by preservice teachers in elementary schools, providing insight into their distinct viewpoints, uncertainties, and questions in education. In the middle of changing teaching methods and educational difficulties, it is crucial to understand the complex problems of new teachers to create efficient teacher training programs and educational plans. This study highlights the need to establish conducive settings for preservice teachers to express their concerns and inquire, promoting introspective behaviors and professional development. The findings provide valuable insights into the continuing discussion on teacher education, suggesting ways to enhance programs, mentorship activities, and policies.